Sand mineralogy of soils parent material from the northeast of Santiago del Estero, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2022)
The northeast of Santiago del Estero province is located in the northwestern edge of the BajosSubmeridionalesbasin (BBSS), in the distal area of the Salado river mega-fan (Fig. 1a). The pre-alluvial substrate in this sector of the Chaco plain is composed by the quartzite sandstones of the Las Piedritas Formation. According to the sedimentary model proposed by Iriondo (1990), the parent materials of the soils are of aeolian, lacustrine and fluvial origin. The genesis of these materials is linked to climatic variations and the neotectonic activity of the Quaternary. The aeolian sediments in the area would correspond to the loess of the Urundel Formation (Iriondo, 1990), which has been characterized by abundant quartz and absence of volcanic glass in the coarse fractions, and illite in the clay fraction.On the other hand, recent studies in the northeast of Santiago del Estero province revealed the presence of pedosediments, which were identified through micromorphological, mineralogical, chemical and physical analyses (Moretti et al., 2020). Unlike the Urundel Formation, soils and pedosedimentary parent materials show different proportions of volcanic glass in the sand fraction, while the clay fraction is composed of illite, kaolinite, and illite-smectite interlayer minerals, among other characteristics. Given the differences in mineralogy and origin between the mentioned sedimentary materials, the aim of this work is to improve the knowledge of the origin of the parent materials and their influence in the soil genesis in this region, through the mineralogical study of the sand fraction. Five soil profiles developed in different landscape positions were studied: an EnticHaplustoll (C-50) and a TypicHaplustoll (C-73) in the alluvial bajada unit; aTypicArgiustoll (C-16) in the slope unit; a TypicHaplustert (C-53) in the flood-plain unit; and a TypicEndoacuert (C-27) in the drainage network (Fig. 1b).The qualitative and quantitative mineralogical study was carried out on the most representative sand fraction (very fine sand: 50-100 µm) by means of optical polarization microscopy. The analysis and interpretation of the mineralogical data was complemented by other previous analytical data (Moretti et al., 2020): granulometry, cation exchange capacity of the clay fraction (CICarc), micromorphology on thin sections, and specific mass magnetic susceptibility (?).The results obtained (Table 1), allowed to identify a paleosurface (P) at the base of the profiles, and two overlying depositional units (UD). UD I includes the pedosediment and UD II consists of a few centimeters thick fine-grained material. A transitional level (UD I-P) between the paleosurface and the pedosedimentwas also differentiated. For all the profiles, the identified minerals were quartz, feldspars, alterites, acid volcanic glass, micas, hornblendes and pyroxenes, in addition to silt-clayey micro-aggregates (pseudo-sands) and grains coated with clay and iron oxides (Fig. 2c; d; e; f y Fig. 3a; b; c; d). In each case, their percentages vary both within the same profile and between profiles, with different trends according to the soil-landscape unit.In the alluvial bajada, the Ap horizons (UD II) of both soils (C-50 and C-73) are characterized by lower contents of volcanic glass than those of the UD I; besides, a high proportion of hornblende is observed in the Ap of the EnticHaplustol. In the pedosediment (UD I), the percentage of volcanic glass increases, and then decreases towards the base of the profiles (P and UD I-P). At the paleosurface level (P), ferromagnesian minerals are very scarce, while quartz increases reaching the maximum values. In correspondence with the decrease of the ferromagnesian minerals, the ? values also decrease towards the base of the profiles. This co-variation suggests that the first magnitude differences in the magnetic signal are related to the mineralogical composition of the parent material.On the other hand, the highest proportion of pseudo-sands and clay-coated grains -as in almost all the profiles- is observed in the pedosediment (UD I). These pseudo-sands and clay-coatings imply an underestimation of the fine fraction content obtained in the granulometric analysis of these materials, which is also revealed by the high and anomalous CICarc values (>100 cmol+.kg-1). A greater degree of alteration of feldspars and the presence of sub-rounded quartz grains covered with iron oxides has also been observed (Fig. 3a; b). This fact also suggests that thismaterial would have been affected by one or more previous cycles of pedogenesisand erosion.The soil studied on the slope (C-16), has the highest content of volcanic glass in the pedosediment (UD I), together with the highest content of ferromagnesian minerals, micas and feldspars. Pseudo-sands increase with depth and decrease at the base of the profile (UD I-P). Surface UD II has not been identified in this soil, which may have been eroded from the slope. Here, the value of ? is also higher at UD I than at the base of the profile, in relation to its higher proportion of ferromagnesian minerals.The Vertisol located in the flood-plain landscape unit (C-53) shows similar mineralogical characteristics than the soils of the alluvial bajada (C-50 and C-73). On the contrary, the Vertisol found in the drainage pathway (C-27) presents a vertical distribution of the components of the coarse fraction that differentiates it from the rest of the profiles in the toposequence. This profile has the highest contents of mica in UD II (Ap-Bt-Btss1), and the highest values of volcanic glass in the UDI(2Btss2-2Bt). It also has a low proportion of pseudo-sands and clay-coated grains throughout the profile, which correlates with low CICarc values. It is interpreted that in this profile the pseudo-sands were not preserved due to the particular hydric conditions in this position of the landscape, the effects of expansion-contraction and the greater degree of soil development. In this profile, higher contents of ferromagnesian minerals have been identified in the UD I and II interface (Btss1 and 2Bt horizons),together with an increase in the ? values.Results suggest a model of landscape-soil evolution that could be related to the environmental changes of the Quaternary in the region. Climatic oscillations and tectonic dynamics during the Late Pleistocene led to readjustment in the hydrographic network of the Salado River, which would have promoted erosion processes of paleosurfaces (P) and generating pedosediments (UD I). The paleosurfaces (P), with high quartz and very low volcanic glass contents, would be related to the sediments of the Salado River and with the quartzite sandstones of the Las Piedritas Formation.The pedosediment (UD I), characterized by the high content of pseudo-sands, would have been enriched in minerals of volcaniclastic origin, which are very scarce in the paleosurface (P). This mineralogical association relates these eolian contributions to the Tezanos Pinto Formation, which covers the landscape in the southern sector of the BBSS basin. Depositional unit II (UD II) is composed of intermediate quartz and volcanic glass contents, and by high mica and hornblendes contents. This unitwould correspond to a youngereolian event that covered the sub-basin surface, probably during some of the arid cycles of the Holocene. This material is not present on the slope unit of the studied sub basin, since it was probably removed by erosion. Finally, under a more humid climate and in a geomorphologically more stable environment, the pedogenesis of these deposits occurred.